Levels and Norm-Development: A Phenomenological Approach to Enactive-Ecological Norms of Action and Perception - Sepúlveda-Pedro, Miguel A. (Frontiers in Psychology, 2020)
The enactive approach and the skilled intentionality framework are two closely related forms of radical embodied cognition that nonetheless exhibit important differences. In this paper, I focus on a conceptual disparity regarding the normative character of action and perception. Whereas the skilled intentionality framework describes the norms of action and perception as the capacity of embodied agents to become attuned (i.e., skilled intentionality) to preestablished normative frameworks (i.e., situated normativity), the enactive approach describes the same phenomenon as the enactment of norms (i.e., as sense-making) at different levels of organization that go from individual biological agents to linguistic encounters. I will argue that although both accounts accurately recognize important features of the norms of action and perception, they also have significant shortcomings. Norm-attunement accurately sees normative, ecological frameworks as the necessary set of constraints for the existence of norms at play in sociocultural bodily practices, but it fails to acknowledge the temporal and open-ended character of these norms and frameworks. Norm-enactment, by contrast, acknowledges that norms of action and perception are temporally open-ended, but fails to explicitly recognize that environmental normative frameworks are necessary for the enactment and development of all sort of norms in the interactional domain of an agent-environment system. To overcome these problems, I propose an enactive-ecological approach to norms of action and perception. This approach consists in describing norm-enactment as a result of a developmental process I call norm-development. This process describes the enactment of norms from the background of ecological, normative frameworks. These frameworks are norms enacted in the past of the interactional history of the agent-environment system that remain open to new configurations (new norms) in the present. To clarify conceptually norm-development, I appeal to Merleau-Ponty’s descriptions of norms of perception, and more particularly to his concept of spatial levels. Like the enactive approach, Merleau-Ponty recognizes that perceptual norms emerge in the interactional history of the agent-environment system, but he also posits that ecological, normative frameworks, that he calls levels, enable and constrain the emergence of perceptual norms and its development.